Ocenjevanje rehabilitacijskih poročil - Brejc, Tone (Psihološka obzorja (Ljubljana), 1996)
In in rehabilitation, being is also a domain of transdisciplinary psychological activity, the written report represents a key document for further actions, but there is no empirical evidence about the quality and satisfactoriness as regard the needs of its users. Therefore, the pilot investigation of the structure and content of the reports prepared by the Vocational Rehabilitation Unit of Rehabilitation Institute, based on the expert analysis and considering the principles and recommandations for psycho logical report writing, was done. It was found that the content of reports was mainly deficient and depending on personal profesional orientation of the reporter, and their quality deminished due to inadequate organisation, vague vocabulary, unclear statement of "the report problem" and overlaping data. The analysis draw attention to the need for evaluation of the expectations of report users, and confirmed the significance and validity of approach, also making possible the suggestions of some rules for "good report writing".
Keywords: rehabilitacija; vocational rehabilitation; poročila; klinična psihologija; kakovost